Theory and applications of models of computation 8th annual conference, TAMC 2011, Tokyo, Japan, May 23-25, 2011 : proceedings - Ogihara, Mitsunori 1963-; Tarui, Jun (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 8th International Conference on Theory and Applications of Models of Computation, TAMC 2011, held in Tokyo, Japan, in May 2011. The 51 revised full papers presented together with the abstracts of 2 invited talks were carefully reviewed and selected from 136 submissions. The papers address the three main themes of the conference which were computability, complexity, and algorithms and are organized in topical sections on general algorithms, approximation, graph algorithms, complexity, optimization, circuit complexity, data structures, logic and formal language theory, games and learning theory, and cryptography and communication complexity.